PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Badan Pendidikan dan Pelatihan Provinsi Jawa Timur Surabaya) - Ismu Cakra Gumilar ; Prof. Dr. Achmad Sudiro, SE., ME. Prof. Dr. Ubud Salim, SE., MA
Keywords: Organization Culture, Work Motivation, Employee Performance _x000D_ _x000D_ The purpose of this research is to know the description of organizational _x000D_ culture, work motivation and employee performance, to know the influence of _x000D_ organization culture on employee performance, to know the influence of organization _x000D_ culture on employee work motivation, to know the influence of work motivation on _x000D_ employee performance, to know the influence of organization culture on employee _x000D_ performance with mediation work motivation in Education and Training Agency of _x000D_ East Java Province with population and all at once with sample are 130 employees. _x000D_ The type of research is expos facto with the type of quantitative research using _x000D_ descriptive explanatory and regression factor analysis. The results of this study _x000D_ indicate that organization culture has a significant effect on employee work _x000D_ motivation. _x000D_ In proving and analyzing it, then used linear regression analysis with F test and _x000D_ T test. The number of samples in this study as many as 130 employees, data